Dielectric properties of Antarctic krill (Euphausia superba) and white shrimp (Penaeus vannamei) during microwave thawing and heating. Issue 1 (2nd January 2017) - Yang, Linxin; Qiu, Weiqiang; Yin, Yalan; Row, Kyung Ho; Cheng, Yudong; Jin, Yinzhe
ABSTRACT: Dielectric properties of Antarctic krill and white shrimp were measured across the microwave frequency range 300–3000 MHz in a temperature range of −20 to 20 °C. To shorten thawing time, the effects of salt, sucrose and moisture contents on dielectric properties at 915 and 2450 MHz were also studied during microwave thawing (MT) and microwave heating (MH). The results indicate that the change in sucrose content had a smaller effect on dielectric properties, and only addition of salt had a significant influence ( p < 0.05) on dielectric properties during MT. Moreover, when these shrimps with addition of a salt–sucrose mixture at 3% w/w were thawed and heated to 20 °C, the microwave processing time was no more than 130 s. Compared with the samples without any additives, thawing time shortened significantly when salt and sucrose were simultaneously added to the samples. Besides, the centre temperature and temperature distribution within the cross section of shrimps confirmed effects of various additives on dielectric properties, suggesting that MT and MH can be applied to the processing of freshwater and oceanic shrimp, and that addition of only salt or the salt–sucrose mixture can further quicken thawing and heating rates to optimize the industrial processing of shrimp.